Influence of Root Exudates and Soil on Attachment of Pasteuria penetrans to Meloidogyne arenaria - Liu, Chang (Journal of nematology, 2017)
The bacterium Pasteuria penetrans is a parasite of root-knot nematodes (Meloidogyne spp.). Endospores of P. penetrans attach to the cuticle of second-stage juveniles (J2) and subsequently sterilize infected females. When encumbered by large numbers of spores, juveniles are less mobile and their ability to infect roots is reduced. This study looked at different factors that influence spore attachment of P. penetrans to the root-knot nematode Meloidogyne arenaria. Pretreatment of J2 with root exudates of eggplant (Solanum melongena cv. Black beauty) reduced spore attachment compared with pretreatment with phosphate-buffered saline (PBS), suggesting that the nematode surface coat was altered or the spore recognition domains on the nematode surface were blocked. Spore attachment was equally reduced following exposure to root exudates from both host and nonhost plants for M. arenaria, indicating a common signal that affects spore attachment. Although phytohormones have been shown to influence the lipophilicity of the nematode surface coat, auxins and kinetins did not affect spore attachment compared with PBS. Root exudates reduced spore attachment more in sterilized soil than in natural soil. Sterilization may have eliminated microbes that consume root exudates, or altered the chemical components of the soil solution or root exudates. Root exudates caused a greater decrease in spore attachment in loamy sand than in a sandy loam soil. The sandy loam had higher clay content than the loamy sand, which may have resulted in more adsorption of compounds in the root exudates that affect spore attachment. The components of the root exudates could have also been modified by soil type. The results of this study demonstrate that root exudates can decrease the attachment of P. penetrans endospores to root-knot nematodes, indicating that when these nematodes enter the root zone their susceptibility to spore attachment may decrease